Rationality, emotions, and ethnicity: Explaining elite political alignments in a deeply divided society - Omar McDoom (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
The role of ethnicity in political behaviour remains unsettled theoretically. Instrumentalist theories emphasize cognitive processes, arguing that political actors strategically employ ethnicity to attain certain goals, while expressivist theories highlight affectual forces, arguing that actors are motivated by the intrinsic emotional power of identity. I show that neither approach adequately explains real-world intra-ethnic and cross-ethnic behaviour. I develop a new theory, integrating rationality and emotion, and argue that they work together in political decisionmaking. Emotional attachment to one's ethnic ingroup biases cognitive judgement against trusting a non-co-ethnic actor. I apply this integrative theory to the political alignment choices of nearly 300 Rwandan opposition elites over a 25-year period and show that it is consistent with the pattern of mono-ethnic and multi-ethnic alignments observed. I additionally analyse the reasons for the historical re-alignments of one political party and interpret interviews with various opposition leaders to reveal their preoccupation with both strategic interests and symbolic identities.
Keywords: D91; 330; political behaviour; rationality; ethnicity; Rwanda